Novel octapeptide as an asymmetric catalyst for Michael reaction in aqueous media - Bayat, Saadi; Abd. Malek, Emilia; Tejo, Bimo Ario; Salleh, Abu Bakar; Mohd Yahaya, Normi; Abdul Rahman, Mohd Basyaruddin (Taylor & Francis, 2013)
In this work, three forms of a novel octapeptide have been evaluated as asymmetric catalysts for the Michael reaction. Low quantity catalyst loading, ecofriendly solvents, and reusability of organocatalyst successfully applied to attain excellent yields and moderate enantioselectivities in the Michael reaction.